Soil biological properties as influenced by long-term manuring and fertilization under sorghum (Sorghum bicolor) -wheat (Triticum aestivum) sequence in Vertisols - INGLE, S S; JADHAO, S D; KHARCHE, V K; SONUNE, B A; MALI, D V (The Indian Journal of Agricultural Sciences, 2014)
The effect of long-term manuring and fertilization on soil biological properties was studied under the long term fertilizer experiment on sorghum [Sorghum bicolor (L.) Moench] -wheat (Triticum aestivum L.) sequence conducted on Vertisols. The treatments comprised 50% RDF, 100% RDF, 150% RDF,100% RDF (-S), 100% RDF + 2.5 kg Zn/ ha to wheat crop only, 100% RD of NP, 100% RD of N, 100% RDF + FYM @ 10 tonnes/ha, 100% RDF + S @ 37.5 kg/ ha, FYM @ 10 tonnes/ha, 75% RDF and control. The assessment of soil biological properties at 40 and 70 days after sowing revealed that, significantly highest CO2 evolution was recorded at 70 DAS of sorghum under 100% RDF + FYM @ 10 tonnes/ ha ( 66.82 mg/ 100 kg). Soil microbial biomass carbon was also influenced significantly with the combined application of NPK+FYM (278.9 mg/ kg). The soil enzyme activity, viz. dehydrogenase (55.01 µg TPF/g/24 hr), urease (47.9 mg NH4/kg/ 24 hr) and cellulase (52.23 µg glucose/g/24 hr) were significantly influenced with the application of 100% RDF + FYM @ 10 tonnes/ha. Similarly, the application of 100% RDF + FYM @ 10 tonnes/ha recorded significantly higher grain yield of sorghum.